OUTCOME AND PROGNOSTIC FACTORS OF STROKE IN CHILDREN PRESENTING AT AN ARMY HOSPITAL IN PAKISTAN: Stroke in Children - Mahmud, Shahid; ., Shahneela; Shah, Sajid Ali (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the outcome and prognostic factors of stroke in children presenting at Military HospitalRawalpindi.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the department of Pediatrics, Military HospitalRawalpindi, from Oct 2012 to Mar 2014.Patients and Methods: Sixty consecutive children presenting with stroke were included in this study after takingwritten informed consent from the guardians/parents. A predesigned proforma was used to record patient’sdemographic details along with the presenting complaints, type of stroke, underlying cause and outcome.Results: The mean age of the patients was 3.49 ± 3.29 (Mean ± SD) years. There were 35 (58.3%) male and25 (41.7%) female children. Ischemic stroke was the most frequent and was observed in 37 (61.7%) patientsfollowed by hemorrhagic (16.7%), sinovenous thrombosis (8.3%) and ischemia with hemorrhagic findings (6.7%).Mixed lesions and transient ischemic attacks were reported in 2 (3.3%) patient each. Mean length of hospitalstay was 9 ± 6 (Mean ± SD) days. Sixteen (26.7%) children recovered completely while 41 (68.3%) children hadsome neurological deficit at discharge. Mild to moderate deficit was recorded in 21 (35.0%) children while 20(33.3%) children had severe deficit. Three (5.0%) patients expired during hospital stay.Conclusion: Ischemic stroke was the most common cause of paediatric stroke. Important risk factors of peadiatricstroke included congenital heart diseases and intracranial infections. Poor prognostic factors included malegender, age less 5 years and congenital heart disease.